Ethics of engagement and insider-outsider perspectives: issues and dilemmas in cross-cultural interpretation. Issue 4 (8th August 2019) - Dhillon, Jaswinder K.; Thomas, Nest
ABSTRACT: This article offers insights into the ethics of engagement and methodological issues and dilemmas in cross-cultural interpretation for researchers who are positioned at different points of the insider-outsider spectrum. The discussion uses examples from qualitative research with Sikh families in Britain and focuses on the design of the methodology and co-interpretation of data from in-depth interviews, both during the interactive data gathering phase and the post-interview analysis and interpretation phase. The researchers represent differing degrees of insider-outsiderness in relation to the British Sikh community; one is a cultural insider (a Sikh) whilst the other is an outsider (non-Sikh). In other respects they share a number of characteristics, including gender, a history of migration, bilingualism and living and teaching in superdiverse communities which all impact on the nature of their engagement with the research participants and with each other as co-researchers. Our reflexive analysis shows that established binary distinctions and polarities in research practice, such as insider/outsider, are inadequate for conceptualizing the fluidity and complexity of the ethics of engagement in co-researching. We argue that both theoretically and empirically a more nuanced conceptualization reflects the realities of multiple researcher positionalities, interpretations and power relations.